Sustainable development law : principles, practices, and prospects - Cordonier-Segger, Marie-Claire (O.U.P. OxfordGB, 2004)
Analyses recent developments in international sustainable development law. Provides a coherent approach which can assist to address conflicts and overlaps between international economic, environmental and social regimes. Surveys the international law related to sustainble development. Discusses proposed principles and presents case studies that examine innovative aspects of key international instruments.